Philosophy of language, Chinese language, Chinese philosophy : constructive engagement - Mou, Bo, 1956- (Philosophy of History and Culture, 2018)
From the constructive-engagement vantage point of doing philosophy of language comparatively, this anthology explores (1) how reflective elaboration of some distinct features of the Chinese language and of philosophically interesting resources concerning language in Chinese philosophy can contribute to our treatment of a range of issues in philosophy of language and (2) how relevant resources in contemporary philosophy of language can contribute to philosophical interpretations of reflectively interesting resources concerning the Chinese language and Chinese texts. The foregoing contributing fronts constitute two complementary sides of this project. This volume includes 12 contributing essays and 2 engagement-background essays which are organized into six parts on distinct issues. The anthology also includes the volume editor's theme introduction on comparative philosophy of language and his engaging remarks for three parts.